The Economic Value of Pollination Services for Seed Production: A Blind Spot Deserving Attention - Arndt Feuerbacher; Theresa Herbold; Falk Krumbe (Environmental and Resource Economics, 2024)
Animal-mediated pollination is important for agricultural seed and crop production, and critical to overall ecosystem health. However, the scientific literature focused on the economic valuation of pollination services has thus far neglected the role of pollination services in seed production. The marketed food output of many crops is not dependent on pollination services, but these crops indirectly depend on pollination services with respect to their seed production. This study proposes a partial equilibrium framework for identifying the value of pollination services. Using Germany as a case study, we find the value of pollination services is about 33% higher when seed production is considered. This increased valuation is driven by two effects: higher seed costs due to high dependence on pollination services, and a higher demand for seeds due to the land expansion needed to mitigate a potential~pollinator collapse. This study demonstrates that more sophisticated approaches are needed to estimate the economic value of pollination services more accurately.
Keywords: 330; Ecosystem services; Economic valuation; Pollinator declines; Seed production; Partial equilibrium analysis; Biodiversity